Sensitivity of Arctic Clouds to Ice Microphysical Processes in the NorESM2 Climate Model ... - Sotiropoulou, Georgia; Lewinschal, Anna; Georgakaki, Paraskevi; Phillips, Vaughan; Patade, Sachin; Ekman, Annica M.L.; Nenes, Athanasios (Zenodo, 2024)
Thermodynamic and microphysical data (matlab files) for NorESM2 simulations presented in the article "Sensitivity of Arctic Clouds to Ice Microphysical Processes in the NorESM2 Climate Model" ...